2013
DOI: 10.4172/2329-888x.1000106
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Serum Total Protein and Immunoglobulin G Concentration in Replacement Dairy Calves

Abstract: Measurement of serum Total Protein (TP) or Immunoglobulin G (IgG) is frequently used within the dairy industry to monitor failure of passive transfer (FPT) in calves. Through such monitoring, modifications to colostrum handling and feeding techniques can be incorporated into farm practices to improve calf management. Most studies establishing cutoff values of TP or IgG for determination of FPT have been based on data primarily obtained from Holstein calves. The purpose of this study was to determine factors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Lower FPT rates seen on the second (16.00%) and third (2.70%) days indicate that immunoglobulins in the colostrum continue to be absorbed by the intestines after 24 h. A similar study conducted in goat kids had similar results [18], where serum IgG concentrations were double on day 4 when compared to day 1 after birth. Furthermore, the serum immunoglobulin levels in calves were reported to be highest at 36 h [11], and even higher immunoglobulin levels have been reported on the 2nd and 3rd days after birth [26]. Colostrum quality of goats in the present study was determined by measurement of IgG and was determined as 4757.53 ± 121.61 mg/dL.…”
Section: Discussionmentioning
confidence: 52%
“…Lower FPT rates seen on the second (16.00%) and third (2.70%) days indicate that immunoglobulins in the colostrum continue to be absorbed by the intestines after 24 h. A similar study conducted in goat kids had similar results [18], where serum IgG concentrations were double on day 4 when compared to day 1 after birth. Furthermore, the serum immunoglobulin levels in calves were reported to be highest at 36 h [11], and even higher immunoglobulin levels have been reported on the 2nd and 3rd days after birth [26]. Colostrum quality of goats in the present study was determined by measurement of IgG and was determined as 4757.53 ± 121.61 mg/dL.…”
Section: Discussionmentioning
confidence: 52%
“…Some authors have established a relationship between BEO supplementation and increased immunity through increased production of immunoglobulins G and M, increasing STP in calves [ 41 , 42 ]. Previous studies confirmed that IgG concentration was lower in calves with severe diarrhea than in healthy calves [ 43 ]. In our study, in addition to serum protein showing no difference between treatments, diarrhea was not a major problem in calves.…”
Section: Discussionmentioning
confidence: 62%
“…We mainly observed the immune status of all calves at the beginning of the trial. Values observed in the three groups exceeded the established limit values for plasma TP (>5.2 mg/dL) and plasma IgG (>1000.0 mg/dL) in Holstein calves, useful for monitoring failure of passive transfer (FPT) in dairy calves [ 29 ].…”
Section: Discussionmentioning
confidence: 99%